Unsuccessful Drug-Resistant TB Treatment Outcomes among Patients with Short-Term Regimen in Central Java, Indonesia - Intan Henda Ardiani; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti; Muhamad Zakki Saefurrohim (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Tuberculosis which shows resistance to various types of drugs poses a significant burden in efforts to prevent and control tuberculosis globally. Since 2020, guidelines from the WHO have recommended a shorter treatment with an all-oral regimen for Drug Resistant Tuberculosis (DR-TB), with the inclusion of bedaquiline instead of an injectable agent. However, the treatment success rate for DR-TB in Indonesia is still low. This study aimed to determine factors contributing to unsuccessful DR-TB treatment using STR in Central Java. This was a nested case-control study of 412 DR-TB patients enrolled with a Short-Term Regimen, registered in 2021 to 2023 who had treatment results in a subset of the Tuberculosis Information System cohort data. Independent variables analyzed included age, gender, patient employment status, history of previous TB treatment, DM status, HIV status, resistance pattern, initial sputum examination results, drug side effects, treatment initiation interval, body mass index, and BPJS ownership status. Statistical analysis was done using SPSS version 22 software, with logistic regression analysis to identify the determinants. The determinant of unsuccessful treatment outcome in Central Java Province which is 51.04% was the positive results of initial sputum examination of treatment (aOR=10.501; 95%CI=5.056-21.807), drug side effects (aOR=1.853; 95%CI=1,000-3.436), obesity (aOR=3.115; 95%CI=1.188-8.166) and BPJS non-possession status (aOR=2.213; 95%CI=0.932-5.255). More strategies are needed to improve the success of treatment with STR.